A Preliminary Study on the Correlation Between Spinopelvic Parameters and Balance in Ankylosing Spondylitis - Emel Ece ÖZCAN EKŞİ and Esra GİRAY and Yeliz BAHAR ÖZDEMİR and İlker YAĞCI and; n GÜNDÜZ (Archives of Rheumatology, 2019)
Objectives: This study aims to identify the relationship between balance and sagittal spinopelvic alignment in ankylosing spondylitis (AS) and compare patients with or without lumbopelvic mismatch in terms of balance. Patients and methods: We enrolled 41 patients (22 males, 19 females; mean age 41.3±8.9 years; range 21 to 57 years) into the study. Sagittal spinopelvic alignment was evaluated measuring thoracic kyphosis, lumbar lordosis, sacral slope, pelvic tilt and pelvic incidence on lateral standing X-rays of the whole spine including the femoral heads. Patients were grouped according to presence of lumbopelvic mismatch (lumbar lordosis- pelvic incidence >10o). Clinical parameters including age, body mass index, pain (Visual Analog Scale), disease activity (Bath Ankylosing Spondylitis Disease Activity Index), and disease duration were recorded. Posture was evaluated measuring tragus-to-wall distance, modified Schober’s test and chest expansion. A computerized pressure plate system (NeuroCom Balance Master®) was used for evaluating static and dynamic balance. Correlations between sagittal spinopelvic alignment parameters and balance were analyzed. Patients with or without lumbopelvic mismatch were compared in terms of balance. Results: Patients took shorter steps, as thoracic kyphosis increased and sacral slope decreased (r= -0.391, p=0.012; r=0.344, p=0.028). Patients with lumbopelvic mismatch had significantly higher sway velocity on firm base with eyes closed and on foam base when the eyes open and closed . They also walked more slowly compared to patients without lumbopelvic mismatch (p>0.05). Conclusion: Lumbopelvic mismatch impaired both static and dynamic balance, while increased thoracic kyphosis and decreased sacral slope impaired only the dynamic balance in patients with AS. Further studies with larger sample size and longer follow-ups need to be conducted to identify the mechanism of spinal deformities and balance disorders in patients with AS.